Students’ Perceptions of the Project Based Learning in Speaking Class at the Ninth Grade - Walhidayah; Muhammad Tahir; Munir; La Sunra; Nur Aeni (Program Studi Magister Pendidikan Bahasa Inggris, Fakultas Bahasa dan Sastra- Universitas Negeri Makassar., 2025)
This study explores students’ perceptions of the implementation of Project-Based Learning (PJBL) in a speaking class. As an instructional approach centered on student-driven projects, PJBL is intended to enhance learners’ engagement, communication skills, and collaborative learning experiences. The research aims to investigate how students at SMPN 2 Barombong respond to the use of PBL in terms of motivation, participation, language development, and speaking confidence. A qualitative approach was employed, using interviews with students from an English as a Foreign Language (EFL) class who had experienced PJBL-based instruction. Data will be collected through in-depth interviews, and documentations with eleventh-grade students at SMPN 2 Barombong using a qualitative research methodology. The findings indicate that students generally perceive PJBL positively, citing increased opportunities to practice speaking in authentic contexts, greater motivation, and improved teamwork skills. However, some students also reported challenges such as time management and unequal group participation. Overall, the study concludes that PBL can be an effective method to develop speaking skills, provided that it is carefully structured and facilitated. These findings offer useful insights for language educators seeking to implement learner-centered strategies in speaking classes.